2009
DOI: 10.1007/978-3-642-03426-8_44
|View full text |Cite
|
Sign up to set email alerts
|

Student Engagement with Peer Assessment: A Review of Pedagogical Design and Technologies

Abstract: Abstract. The paper summarizes participatory action research that explores student attitudes towards a peer assessment exercise and further reveals a distinctive pattern in student responses. A formative and reciprocal peer assessment exercise was studied to identify possible reasons for low levels of student participation. The target group included students in an undergraduate course in computing. A follow-up questionnaire, undertaken by 36 students, was analyzed and compared against assignment marks. Finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 12 publications
2
14
0
1
Order By: Relevance
“…Moreover, the students in this study highly valued peer assessment confirming the study by [14] and [15].…”
Section: Advances In Social Science Education and Humanities Researcsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, the students in this study highly valued peer assessment confirming the study by [14] and [15].…”
Section: Advances In Social Science Education and Humanities Researcsupporting
confidence: 86%
“…Peer assessment has been considered beneficial in promoting student learning, enhancing student understanding on the work they should make, and improving student performance [12] [13]. A number of studies have shown positive perception of students with regard to peer assessment [14][15].…”
Section: Introductionmentioning
confidence: 99%
“…These types of activities must be properly selected in order to encourage students' participation (Villalobos, 2003); classroom activities are also important to get students involved in the learning process (Stepanyan et al, 2009). …”
Section: Activities and Resources For Teaching Listening And Speakingmentioning
confidence: 99%
“…Research reports that interpersonal variables, in the absence of anonymity, likely moderate how students apply the peer review procedure (Van Gennip, Segers, & Tillema, 2009;Stepanyan et al, 2009). More precisely, factors such as peer pressure and fear of disapproval when assigning low scores can affect the outcomes of classmates' respective assessments.…”
Section: Mismatch: Expectations Vs Experiencementioning
confidence: 99%
“…In principle, by creating systematic opportunities for classmates to assess and constructively criticize each other's works, the peer review process reportedly promotes engagement on a variety of intellectual, social, and operational fronts. Completing the assigned responsibility of formally assessing their classmates' work, an often unprecedented charge, promotes several drivers of student engagement, including motivation, reflection, autonomy, self-efficacy, diplomacy, problem-solving, and responsibility (Boud & Falchikov, 2007;Stepanyan, Mather, Jones, & Lusuardi, 2009). Done well, Mulder, Pearce, and Baik (2014) conclude, peer reviews "nurture an impressively wide array of generic skills related to giving and accepting criticism, which are of fundamental importance in any professional workplace.…”
Section: Introductionmentioning
confidence: 99%